DYNAMIC CONTROL OF DISTANCE EDUCATION PROGRESS ON EXAMPLE OF CHESS PROBLEMS - Кравцова, Маргарита; Захаров, Виктор (SWorldJournal, 2020)
The paper considers the ways to range progress of students in the distance education system Chess King. The basic idea is in using Elo rating system. The article offers a new formula that uses success percent for every exercise instead of solved/not sol